The History of Islam in Kashmir: A Special Focus on Sufi Saint Shaikh-ul-‘Āalam’s Socio-religious Impact on the Kashmir Valley - Lone, Rameez Ahmad; Aziz, Yasmeena; Haq, Syamsul; Poovadichalil, Muhammed Nishad Maliyakkal; Maliki, Noval (Jurnal Iman dan Spiritualitas, 2025)
This paper explores the rich history of Islam in the Kashmir Valley, with a particular focus on the socio-religious impact of the revered Sufi saint Shaikh-ul-‘Āalam It traces the early Islamic presence in Kashmir, shaped by figures like Hazrat Bulbul Shah and Hazrat Shah-i-Hamdaan, and explores the unique integration of Islam in the region, distinct from other South Asian experiences often marked by conquest and trade. The study highlights key milestones, including the pivotal role of Sufi missionaries in embedding Islamic practices and laws. Central to the paper is the transformative influence of Shaikh-ul-‘Āalam, whose teachings and poetry addressed social justice, ethical reform, and environmental consciousness while promoting Islamic monotheism. His engagement with indigenous traditions, particularly the Rishi order, further enriched Kashmir’s spiritual and cultural landscape. Utilizing a library or literature study research methodology, the study relies on secondary data and thematic analysis to critically explore Shaikh-ul-‘Āalam’s enduring legacy. The findings highlight his pivotal role in fostering a harmonious and inclusive society, emphasizing his lasting impact on Kashmir's religious and cultural identity.